2006
DOI: 10.1517/14656566.7.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the treatment of interstitial cystitis

Abstract: Recent years have brought dramatic advances in the clinician's ability to offer effective pharmacotherapy to patients who have interstitial cystitis. Medical treatments have been developed and applied to reduce the interstitial cystitis symptoms of pelvic pain and urinary urgency/frequency, and to address underlying causes of the disorder. In addition, advances in the understanding of the natural history of interstitial cystitis have revealed that it is insidiously progressive and the classical definition--rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…Our observations of pelvic pain relief following intravesical lidocaine administration are consistent with clinical findings where patients with severe IC experience temporary relief of pelvic pain by instillation of 2% lidocaine into the bladder (27). In addition, we found that colonic lidocaine relieves pelvic pain associated with neurogenic cystitis, an observation that is reminiscent of irritable bowel patients who experienced relief of both rectal symptoms and abdominal pain from lidocaine administered to the colon (36,37).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our observations of pelvic pain relief following intravesical lidocaine administration are consistent with clinical findings where patients with severe IC experience temporary relief of pelvic pain by instillation of 2% lidocaine into the bladder (27). In addition, we found that colonic lidocaine relieves pelvic pain associated with neurogenic cystitis, an observation that is reminiscent of irritable bowel patients who experienced relief of both rectal symptoms and abdominal pain from lidocaine administered to the colon (36,37).…”
Section: Discussionsupporting
confidence: 88%
“…One clinical treatment that offers temporary relief of chronic pain in patients with IC is instillation of 2% lidocaine directly into the bladder (27). This treatment modality presumably works by quelling C-fiber activity associated with IC bladder pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
“…Visceral pain originating from inflamed bladder can be relieved by use of local anesthetics such as lidocaine 2,3. The present study evaluated the effects of lidocaine on referred mechanical hyperalgesia (as opposed to visceral pain per se), and results indicate that pre-treatment with lidocaine prevents referred hyperalgesia that accompanies cystitis.…”
Section: Discussionmentioning
confidence: 91%
“…Local anesthetics have been used extensively to prevent or minimize pain that accompanies cystitis 1,2. Lidocaine primarily blocks generation and propagation of action potentials through direct binding of neuronal voltage-gated sodium channels thereby producing analgesia by inhibiting excitation of nerve endings or blocking conduction in peripheral nerves 3.…”
Section: Introductionmentioning
confidence: 99%
“…Oral therapy included administration of analgesics, anticholinergics, anticonvulsives, antidepressants, and hypnotics; the intravesical drug was heparin [17] . Urodynamic examination was performed by two physicians according to the International Continence Society (ICS) and ESSIC standards [18,19] .…”
Section: Examinationmentioning
confidence: 99%